2005
DOI: 10.1038/sj.ejcn.1602296
|View full text |Cite
|
Sign up to set email alerts
|

Zinc intake and status in middle-aged and older European subjects: the ZENITH study

Abstract: Objective: Inadequate intakes of micronutrients in elderly negatively affect the nutritional status. Zinc is an essential micronutrient in the elderly, especially in relation to its impact on immune function, bone mass, cognitive function and oxidative stress. However, data are lacking on zinc intake and status during normal ageing. In this study, we evaluate the intake and status of zinc in late middle-aged and older free-living subjects. Design: Dietary zinc intake and zinc status in 188 middle-aged subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
2
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 28 publications
6
58
2
6
Order By: Relevance
“…In SU.VI.MAX, the average serum zinc concentrations of men and women were close to those obtained from the Second National Health and Nutrition Examination Survey in the United States (Mares-Perlman et al, 1995; The Age-Related Eye Disease Study Research Group, 2002;Hotz et al, 2003) and from European studies in middle-age and/or senior healthy subjects (Andriollo-Sanchez et al, 2005;Marcellini et al, 2006). Our results show that serum zinc concentration is significantly lower in women compared with men.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In SU.VI.MAX, the average serum zinc concentrations of men and women were close to those obtained from the Second National Health and Nutrition Examination Survey in the United States (Mares-Perlman et al, 1995; The Age-Related Eye Disease Study Research Group, 2002;Hotz et al, 2003) and from European studies in middle-age and/or senior healthy subjects (Andriollo-Sanchez et al, 2005;Marcellini et al, 2006). Our results show that serum zinc concentration is significantly lower in women compared with men.…”
Section: Discussionsupporting
confidence: 63%
“…Serum zinc concentration significantly decreased in fasting US men after 60 years whereas a tendency to increase was noted from 40 to 65 years in fasting US women. These variations remained moderate as previously described in free-living population (Savarino et al, 2001;Andriollo-Sanchez et al, 2005) in contrast to the dramatic decrease in serum zinc concentration observed in institutionalized elderly (Pepersack et al, 2001). The lower values in non-menopausal women taking oral contraceptive was also confirmed (Hotz et al, 2003;Akhter et al, 2005;Fallah et al, 2009), which suggests that gender differences could be partly attributed to hormonal status and/or contraceptive steroids intake.…”
Section: Discussionmentioning
confidence: 41%
“…The indices of zinc nutritive status (namely, zinc intake and biochemical status measures) in the older European adults in the present study, as discussed in more detail by Andriollo-Sanchez et al (2005), were, in general, relatively good and there was a low prevalence of zinc deficiency (B5-6%) in this population. Zinc intake was positively correlated with urinary zinc as well as with serum zinc levels.…”
Section: Discussionsupporting
confidence: 53%
“…Andriollo-Sanchez et al (2005), in this Supplement, have shown that Zn status among the samples here are all within normal ranges. Findings in this area have pinpointed noticeable depletions in Zn during extreme poor moods of depression (Maes et al, 1997).…”
Section: Discussionmentioning
confidence: 51%